Competing electrophilic substitution and oxidative polymerization of arylamines with selenium dioxide - Selladurai, Vishnu; Karuthapandi, Selvakumar (Beilstein Journal of Organic Chemistry, 2024)
This article describes the detailed analysis of the reaction between arylamines, such as aniline, o-anisidine, and methyl anthranilate, with selenium dioxide in acetonitrile. A systematic analysis of the reaction products with the help of 77Se NMR and single-crystal X-ray crystallography revealed that the reaction progress follows three major reaction pathways, electrophilic selenation, oxidative polymerization, and solvent oxidation. For aniline and o-anisidine, predominant oxidative polymerization occurred, leading to the formation of the respective polyaniline polymers as major products. For methyl anthranilate, the oxidative polymerization was suppressed due to the delocalization of amine lone pair electrons over the adjacent carboxylate function, which prompted the selenation pathway, leading to the formation of two of the isomeric diorganyl selenides of methyl anthranilate. The diaryl selenides were structurally characterized using single-crystal X-ray diffraction. Density functional theory calculations suggest that the highest occupied molecular orbital of methyl anthranilate was deeply buried, which suppressed the oxidative polymerization pathway. Due to solvent oxidation, oxamide formation was also noticed to a considerable extent. This study provides that utmost care must be exercised while using SeO2 as an electrophile source in aromatic electrophilic substitution reactions.
Keywords: arylamines; electrophilic substitution; oxamides: polymerization; selenium dioxide